Studying The Relationship Between The Written Premiums And Profitability In The Syrian Private Insurance Companies During (2008-2017) - حسن رانيا (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to analyze the development of written premiums in the private insurance companies in Syria during (2008-2017). we were used return on assets and return on equity as profitability index to identify the impact of written premiums on profitability by using The results of this research have indicated positive statistically significant relationship between the written premiums and the return on equity, while the effect of written premiums wasn’t significant on the return on assets. The previous conclusion has been reached by Using Panel data namely pooled regression model (PM).